UNDERSTANDING MOLECULAR BONDING AND GEOMETRY THROUGH FLIPPED CLASSROOM IMPLEMENTATION - Sri Mulyanti; Mutista Hafshah; Nana Misrochah (Jurnal Pengajaran MIPA, 2021)
Understanding molecule bonding and geometry are essential requirements in learning organic chemistry. Studies found that students cannot fully grasp the meaning of these abstract concepts, and pandemic conditions become an added challenge for learning organic chemistry virtually. In this study, We implement flipped classroom model for teaching organic chemistry, particularly for molecule bonding and geometry. Results indicated the benefit of the flipped classroom for students' improved understanding, and advanced analysis for several learning aspects also corroborated this finding.